Immunomodulatory effects of palm oil-derived delta-tocotrienol on microglia responses - Tan, Shi Wei (2017)
Microglia are the main immunocompetent cells of the central nervous system (CNS). The chronic inflammatory responses of microglia can lead to significant neuronal damage. Thus, strategies to control microglia activation provide an alternative therapeutic approach for neuroinflammatory diseases. Vitamin E, namely the tocopherols and tocotrienols, are potent antioxidant and anti-inflammatory compounds. Importantly, tocotrienols confer higher protection against glutamate- induced neurotoxicity compared to tocopherols. BV2 microglia pre- treated with delta-tocotrienol (-tocotrienol) showed highest reduction in NO production compared to treatment with alpha- (-) and gamma- (-) isomers. This current study explores the modulatory function of - tocotrienol on microglial inflammatory responses, mainly by using primary mouse microglia cultures.